Malaysia Science Academy visited UMP - UMP, PNC
A 20 member delegation from the Malaysia Science Academy (MSC) and academicians from local and abroad visited Universiti Malaysia Pahang (UMP) to hold discussion and share expertise in research findings on May 8, 2012.